Raavanan - Rahman, Allah R. 1966- (Rapid Eye Movies, 2011)
Dev Prakash Subramaniam is assigned the task of apprehending a bandit, Veeraiya, and accordingly re-locates with his wife, Ragini. Shortly thereafter, while investigating another matter, he will be notified that his wife has been abducted by Veeraiya. He, in the company of several well-armed policemen, and guided by a forest guard, will relentlessly pursue this elusive bandit who is both revered and feared by the local residents; while Ragini will find out the real reason behind her abduction